IMPLEMENTASI SCRUM DALAM PENGEMBANGAN SISTEM INFORMASI AKADEMIK DI SDN KEDAUNG WETAN 6 TANGERANG - Sari, Yunita; Rudianto, Biktra (LPPM Universitas Bina Bangsa, 2023)
Kedaung Wetan 6 SDN today still relies on a manual system in managing academic data, which often poses barriers such as inaccurate data, slow processes, and difficulties in accessing information. The research aims to design and develop web-based academic information systems that are more efficient and effective in addressing such problems. The system development adopted the Scrum method using PHP technology, framework CodeIgniter (CI) and MYSQL. With Scrum, the system development was gradually carried out in short sprints, enabling the team to adapt to changing needs and deliver faster results. The academic information system produced is expected to include features such as student data management, teacher data, student ratings and absences. Thus, this system will be expected to improve the efficiency of the work of teachers and administrative staff, facilitate access to information for all stakeholders, and improve the quality of educational services in SDN Kedaung Wetan 6